Identification method of determining differential equations controlled by computers - Иванова, Л. Н. (Proceedings of National Aviation University (archive), 2000)
Worked out is identification method for obtaining a digital mathematical model in the form of differential equations. The identification method lies in transformation of differential equations system into equivalent differential equations and in calculation of coefficients of these equations by the results of precise simulation of differential equations under influence of special form signals